Smart parking based on IOS apps for smart cities - Atiqur Rahman,; Ufiteyezu, Emmanuel (Penerbit Universiti Kebangsaan Malaysia, 2023)
Parking problem has become a big problem for us in daily life. Mainly in urban and city corporation area like mall, market etc. we face this problem more and finding space for parking here is very difficult. As a result, we spend a lot of time and energy. Finding a parking space has become a much more frustrating event for the driver or user. If the users or drivers do not get any parking space and park their vehicles randomly anywhere then the road will be jammed and the safety of the vehicles will be threatened. It is also the cause of many accidental incidents. It is the manual system that we usually see. We need a smart parking system that will play a role in creating the smart city of the future. We propose an iOS apps-based parking system to solve this problem of manual system. It allows users or drivers to find parking spaces and park their cars through mobile apps i.e., our developed iOS apps for smart parking. Then we do a comparative analysis of our system with the manual system with direct participation of users and see if our system is used then the existing problems will no longer exist.